Abusive Policies : How the American Child Welfare System Lost Its Way - Raz, Mical (Studies in social medicine., 2020)
"In the early 1970s, a new wave of public service announcements urged parents to 'help end an American tradition' of child abuse. The message, relayed repeatedly over television and radio, urged abusive parents to seek help. Support groups for parents, including Parents Anonymous, proliferated across the country to deal with the seemingly burgeoning crisis. At the same time, an ever-increasing number of abused children were reported to child welfare agencies, due in part to an expansion of mandatory reporting laws and the creation of reporting hotlines across the nation. Here, Mical Raz examines this history of child abuse policy and charts how it changed since the late 1960s, specifically taking into account the frequency with which agencies removed African American children from their homes and placed them in foster care"--